Experientia and the Machiavellian turn in religio-political and scientific thinking: Basel in 1580. Issue 7 (2nd October 2016) - Almási, Gábor
SUMMARY: This study is centred on events in 1580 surrounding a scandalous publication of Machiavelli's The Prince by Pietro Perna in Basel. With the presentation of new documents the paper fully reconstructs the judicial case that followed its publication, raising new questions about the author of the infamous book Vindiciae contra tyrannos . However, this fascinating story will serve only as a starting point for the investigation of Machiavelli's late-sixteenth-century reception, providing insights into not only the political and religious but also the scientific context of its publication. These fields, it will be argued, were thoroughly interrelated, all sharing similar epistemological premises.